Effect of Problem-Based Learning on the Student Problem-Solving Skills - Nurvita Putri Utami; Fitria Wulandari (Jurnal Pijar MIPA, 2026)
Science learning in elementary schools is expected to not only provide conceptual understanding but also foster students' ability to solve real-life problems through active learning. This study was conducted to measure the effect of Problem-Based Learning on the problem-solving ability of fifth-grade students of SDN Krembung 1 in learning science on the human respiratory system. The One Group Pretest-Posttest research design was used to test the instrument's validity and reliability, assess the normality and homogeneity of the pretest and posttest results, and determine the influence using the T Test. The instrument developed by the researcher was based on the problem-solving indicators developed by George Polya: (1) Understanding the problem, (2) Planning Problem Solving, (3) Implementing the problem-solving plan, and (4) Checking the Process and Results of problem solving. Problem-Based Learning is applied through five stages, namely: (1) Orientation to the problem, (2) organising students, (3) guiding the investigation, (4) developing and presenting results, and (5) analysing and evaluating the problem-solving process. The pretest was carried out first, followed by the application of the problem-based learning model, and then the posttest. The average pretest score was 79 (68–89), and the average posttest score was 90 (75–100). The results of the paired sample t-test analysis showed a significance value (2-tailed) of 0.000, which means there is a significant difference between the pretest and posttest results. These findings suggest that integrating Problem-Based Learning into classroom instruction not only enhances students’ problem-solving abilities but also aligns well with the goals of competency-based curricula such as the Merdeka Curriculum, which emphasize active learning and critical thinking. Thus, Problem-Based Learning is effective in improving students' problem-solving abilities.